Indian givers : - Weatherford, J. McIver (Crown Publishers, 1988)
After 500 years, the world's huge debt to the wisdom of the Indians of the Americas has finally been explored in all its vivid drama by anthropologist Jack Weatherford. He traces the crucial contributions made by the Indians to our federal system of government, our democratic institutions, modern medicine, agriculture, architecture, and ecology, and in this astonishing, ground-breaking book takes a giant step toward recovering a true American history.